2010
DOI: 10.1016/j.ijdevneu.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Genistein as a neuroprotective antioxidant attenuates redox imbalance induced by β‐amyloid peptides 25–35 in PC12 cells

Abstract: GEN could alleviate the oxidative stress caused by Abeta25-35 treatment and maintain redox balance in PC12 cells, which might be associated with the regulation of Nrf2/HO-1 signal pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 34 publications
4
56
0
Order By: Relevance
“…Moreover, we found that expression of cytochrome c and Puma were reduced, alongside with the restoration of Bcl-2/Bax and Bcl-xL/Bax ratio in the presence of biochanin A, which led to a decrease in the apoptotic rate. These data demonstrate that mitochondria are involved in the protective effect of biochanin A against Aβ [25][26][27][28][29][30][31][32][33][34][35] and that this drug attenuated Aβ 25-35 -induced PC12 cell injury and apoptosis by preventing mitochondrial dysfunction. Thus, biochanin A might raise a possibility as a potential therapeutic agent for Alzheimer's disease and other related neurodegenerative diseases.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Moreover, we found that expression of cytochrome c and Puma were reduced, alongside with the restoration of Bcl-2/Bax and Bcl-xL/Bax ratio in the presence of biochanin A, which led to a decrease in the apoptotic rate. These data demonstrate that mitochondria are involved in the protective effect of biochanin A against Aβ [25][26][27][28][29][30][31][32][33][34][35] and that this drug attenuated Aβ 25-35 -induced PC12 cell injury and apoptosis by preventing mitochondrial dysfunction. Thus, biochanin A might raise a possibility as a potential therapeutic agent for Alzheimer's disease and other related neurodegenerative diseases.…”
mentioning
confidence: 64%
“…However, pretreatment with biochanin A prevented the Aβ 25-35 -induced downregulation of both anti-apoptotic proteins and upregulation of Bax, resulting in an increase in both expression ratio. In the case of cytochrome c and Puma, Aβ [25][26][27][28][29][30][31][32][33][34][35] causes approximately 2-fold increase in their expression (194.54%˘7.17% and 206.07%˘13.54% respectively) compared with the control group. Conversely, as shown in Figure 6C,E, their expression was decreased in a dose-dependent manner in the presence of biochanin A.…”
Section: Effect Of Biochanin a On The Expression Of Pro-and Antiapoptmentioning
confidence: 92%
See 1 more Smart Citation
“…A lack of heme oxygenase 1, an endogenous enzyme that is induced in neurons in response to oxidative and other stress and stimulates the degradation of pro-oxidant heme into free iron, carbon monoxide and biliverdin and/or the anti-oxidative bilirubin, may also be associated with increased neural damage from ischaemic strokes [103], as well with Alzheimer's disease and Parkinson's disease [104]. Heme oxygenase 1 is dose-and time-dependently induced by resveratrol, which may provide another cerebrovascular and neuroprotective effect for phenolic compounds.…”
Section: Haemostasis and Oxidative Stressmentioning
confidence: 99%
“…Isoflavones are secondary plant metabolites, a group of natural bioflavonoids synthesized exclusively by the Leguminosae (Fritsche & Steinhart, 1999), and they are associated with the risk reduction or prevention of various diseases, such as breast cancer and prostate cancer (Liggins et al, 2000), cardiovascular disease (Rimbach et al, 2008), and estrogenic and antioxidant activity (Liu, Kanjo, & Mizutani, 2010;Ma et al, 2010). Twelve isoflavone forms have been reported in soybeans, including three aglycones: genistein, daidzein and glycitein and their respective 7-O-β-D-glucosides (genistin, daidzin and glycitin), 6"-O-malonyl-7-O-β-D-glucosides (malonylgenistin, malonyldaidzin and malonylglycitin) and 6"-O-acetyl-7-O-β-Dglucosides (acetylgenistin, acetyldaidzin and acetylglycitin (Shao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%